Australian and New Guinean Stingless Bees of the Genus Austroplebeia Moure (Hymenoptera: Apidae)—a revision - Dollin, Anne E.; Dollin, Leslie J.; Rasmussen, Claus (Zootaxa, 2015)
The stingless bee genus Austroplebeia Moure occurring in Australia and New Guinea is revised, based on a morphological analysis of samples from 177 colonies. Five species are recognised: A. cincta (Mocsáry), A. essingtoni (Cockerell), A. australis (Friese), A. cassiae (Cockerell) and A. magna, sp. nov. Three different colour morphs of A. australis are described. Five new synonymies are proposed: A. cockerelli (Rayment), A. ornata (Rayment), A. percincta (Cockerell) and A. websteri (Rayment) = A. australis; A. symei (Rayment) = A. cassiae. Workers, males and queens are described for all species. Populations of A. cincta, recently found in Queensland, Australia, are compared with A. cincta from the type locality and other areas in New Guinea. A lectotype is designated for A. percincta (Cockerell). Provenance of type material is discussed. A key to the species, distributions and nest descriptions are provided.